2021
DOI: 10.3390/jcm10081771
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies against SARS-CoV-2 in Children with Juvenile Idiopathic Arthritis a Case-Control Study

Abstract: There is limited data on the effect of the novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) on pediatric rheumatology. We examined the prevalence of antibodies against SARS-CoV-2 in children with juvenile idiopathic arthritis (JIA) and a negative history of COVID-19 and the correlation of the presence of these antibodies with disease activity measured by juvenile arthritis disease activity score (JADAS). In total, 62 patients diagnosed with JIA, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our previous study conducted during the first wave of the COVID-19 pandemic (from 1 June to 30 September 2020), with a confirmed number of cases from 362 to 1405 per day/39.3 million inhabitants, the prevalence of anti-SARS-CoV-2 antibodies in children with JIA was assessed [ 4 , 7 ]. At that time, lower seropositivity in children with JIA (12.9% positive in at least one of the antibodies IgA or IgG) and a slightly higher seropositivity in healthy children was noted [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study conducted during the first wave of the COVID-19 pandemic (from 1 June to 30 September 2020), with a confirmed number of cases from 362 to 1405 per day/39.3 million inhabitants, the prevalence of anti-SARS-CoV-2 antibodies in children with JIA was assessed [ 4 , 7 ]. At that time, lower seropositivity in children with JIA (12.9% positive in at least one of the antibodies IgA or IgG) and a slightly higher seropositivity in healthy children was noted [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in children with rheumatic diseases have been conducted in other countries [ 8 , 9 , 10 ]. In a study conducted in Turkey from March 2020 to August 2020 [ 8 ], exactly in the period of our first study [ 4 ], 149 children asymptomatic for COVID-19 (43 healthy children, 42 with JIA, and 64 with other rheumatic diseases) were included. The proportion positive for anti-SARS-CoV-2 IgA or IgG was 12.75% children, including 18.6% healthy children and 11.9% diagnosed with JIA, but those differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 76 ] Poland Case–Control Study 12(2–18) JIA 62 - JIA patients do not exhibit a higher seroprevalence of anti-SARS-CoV-2 antibodies than healthy individuals. [ 82 ] Turkey Single-center, retrospective study 12 JIA, FMF, systemic autoinflammatory diseases 87(37–50) - Children with rheumatic diseases do not have a higher chance of developing severe COVID-19. - The disease's severity is unaffected by biological treatment.…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…These findings support that patients in whom JIA is stably controlled by biologics without/with low‐dose prednisolone show favorable outcomes. Opoka‐Winiarska et al 8 reported that eight JIA patients on immunosuppressive therapy with no history of infection had anti‐SARS‐CoV‐2 antibodies, although 62 JIA patients did not have a higher seroprevalence of anti‐SARS‐CoV‐2 antibodies than 32 healthy children. In this setting, a more asymptomatic or less symptomatic infection of SARS‐CoV‐2 may occur in pediatric patients with RMDs than we expected.…”
Section: Case 1 2 3 4 5 6mentioning
confidence: 99%